Examining the role of intellectual property law in Kenya's oil and gas sector - Mwaura, Caroline Wambui (Department of Commercial Law, 2020)
This thesis analyses how Kenya should apply intellectual property (IP) law in the country’s oil and gas sector to foster innovation and support economic growth within the context of the country’s development plan, Kenya Vision 2030. Specifically, the thesis considers the possible influence of IP law on innovation, investment and economic growth in the oil and gas sector in Kenya. Using doctrinal methodology, the thesis examines legislation and case law from Kenya, South Africa and the United Kingdom relating to competition and protection of patents, copyright, trade marks, trade secrets and industrial designs. This examination is based on a public interest approach to IP law and competition law and seeks to determine the possible effect of Kenya’s IP laws on investment and innovation in the sector. The study finds that IP law and competition law reflect an attempt to accommodate public interest and the interests of investors. It argues that regulation of Kenya’s oil and gas sector using IP law is likely to enhance innovation and support economic growth if relevant IP laws provide for protection of IP whilst safeguarding public interest. The thesis also finds that protection of traditional knowledge (TK) is likely to be relevant to the upstream oil and gas sector in Kenya for environmental resource management. It argues that optimal management of TK is likely to entail collaborative work between indigenous communities, public institutions and private enterprises, as provided for in Kenya’s Environmental Management and Coordination Act (Number 8 of 1999). The thesis makes proposals for a regulatory environment that is likely to provide a firmer basis for investment in the country’s oil and gas industry, promote competition in markets for IP in Kenya, provide a sustainable IP law framework for the sector for economic growth in Kenya, preserve TK of local communities and enhance equitable sharing of benefits related to TK in the context of the country’s oil and gas industry. The thesis contributes to literature on Kenya’s oil and gas industry by filling the apparent gap in analysing the possible effect of the country’s IP law on investment in the industry and public interest.